Differentiated or â€œIndividualâ€ Teaching for Children with Special Needs, now a Necessary Reality Even in Albanian Education - Duka, Ambera; Tati, Ermira (Mediterranean Journal of Social Sciences, 2012)
The goal of this research is to treat the necessity of the differentiated teaching in the included classes. Mostly based on theskills and needs of the children with special needs it places the teaching method on individual bases. This study will be a qualitativestudy .Its data are collected from the observations and interviews with the teachers of the primary schools in our city Durres. From thefigures received by the Local Education Authority in Durres it is noticeable that there is a vast growth of the numbers of the pupils withspecial needs year by year. The opinions and suggestions given ,which do not pretend to be the solution of the problems fordifferentiated teaching , but it is hopeful to infleunce more or less on the lessen of the problems.Practice has shown that with apersistent work and the collaboration of all , on the condition that every difficulty can be undergone successfully though it may seemunsolveable.